EFEKTIVITAS PENGGUNAAN MEDIA TABUNG ANGKA TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK SEKOLAH DASAR - Vannesa Almayra Nugroho; Baihaqi Syaichul Islam; Falihatin Anjani; Wulan Sutriyani (Jurnal Karya Pendidikan Matematika, 2023)
It has become a necessity for students to understand Mathematics, especially additional material. Problems or obstacles in the learning process often occur, especially in Elementary Schools with Mathematics Learning which require high creative thinking power to master the material. The purpose of this study was to determine the effectiveness of using number tube media on the results of learning Mathematics in addition material for grade 1 students of SDN 6 Pecangaan. The method used is a quantitative experiment with the type of Pre-Experimental research. The research design used was the One-Group Pre-test Post-test Design. Data collection was carried out using a test instrument. For data analysis, tests for normality, homogeneity, and hypotheses were carried out using the SPSS 25 program. The results showed that the use of numeric tube media was effective in improving the results of learning mathematics in addition material in grade 1 students at SDN 6 Pecangaan. Evidenced by the results of the hypothesis test Thitung 27.970 > Ttabel 1.701. So it can be interpreted that H0 is rejected while Ha is accepted. The average pretest result was 66 after the use of number tube media was carried out posttest with the average student learning result was 98.